Head-to-Head Comparison of Etanercept vs. Adalimumab in the Treatment of Ankylosing Spondylitis: An Open-Label Randomized Controlled Crossover Clinical Trial - Wei, James Cheng-Chung; Tsou, Hsi-Kai; Leong, Pui-Ying; Chen, Chia-Yin; Huang, Jin-Xian (Frontiers in Medicine, 2020)
ackground: Anti-tumor necrosis factor (TNF) biological agents had been proved to have dramatic effect in ankylosing spondylitis (AS). We aimed to determine the efficacy and safety of crossover effects of adalimumab versus etanercept in AS patients. Methods: A randomized open label crossover study was done in patients with active AS. Patients were randomized into two sequence groups, etanercept first (treatment arm) versus adalimumab first (control arm) 8 weeks and then switch over for another 8weeks.The primary endpoints were difference of Bath AS activity index (BASDAI) and AS disease activity score (ASDAS)crp at week 16. Secondary endpoints were ASDASesr, ASAS20 and ASAS40 response rate and the proportion of patients achieving ASDAS inactive disease (ID) and low disease activity (LDA) at week 8and 16.Patient global assessment and preference was grading on a numerical scale. Results: A total of 21patientswere screened and 19 of them were randomly allocated into treatment arm (n=9) and control arm (n=9). At baseline, age, sex, BASDAI and ASDAS of both arms were comparable (p>0.05). Both arms showed dramatically improvement while no significance was observed between the changes of ASDAScrp (0.90 1.39 vs 1.24 1.40 at week 8, p=0.612; 1.02 1.22 vs 1.26 1.44 at week 16,p=0.707, respectively). ASAS20 and ASAS40 response were also comparable at week 8 (33% vs 44%, p=1.000; 22% vs 22%, p=1.000) and week 16 (22% vs 22%, p=1.000; 22% vs 22%, p=1.000), respectively. Both arms were well tolerated without serious adverse event. Adalimumab was relatively more favorable by patients in both arms with total mean grading score of 0.4 (-5~5, p=0.218). Conclusion: Etanercept and adalimumab can both dramatically improve disease activity in 16 weeks. Crossover administration of etanercept and adalimumab revealed comparable efficacy and safety. Trial Registration: The protocol was approved by the Institutional Review Board with the register CS08019 from Chung Shan Medical University Hospital (CSMUH), Taichung, Taiwan and registered at ClinicalTrials.gov Protocol Registration and Results System: NCT02489760.